Дослідження замків Закарпаття у 2009 р. - Прохненко, І.А.; Гомоляк, О.М.; Зомбор, І.Т. (Археологічні дослідження в Україні, 2010)
The Mediaeval Group of the expedition of the Uzhhorod National University studied Siltse and Kvasove castles in Zakarpattya Oblast. The preliminary date of the beginning of functioning of the castle in Siltse village was determined as the 13th c., while the castle in Kvasove village was referred to the 16th c. The existence of the Late Bronze Age horizons at these sites is also evidenced.